MATHEMATICAL DISTRIBUTION MODELING PASSENGER FLOWS ON DOMESTIC LINES ON MAIN AIRPORTS OF UKRAINE IN THE FORECAST PERIOD - Kozlyuk , I. O. (Problems of Informatization and Control, 2021)
The forecast distribution of passenger flows to each of the main airports of Ukraine has been determined in order to satisfy the population by air. The presented calculations allow to determine the required number of promising aircraft on domestic airlines.